Engineered Fiber Based Lost Circulation Pill to Abridge Lost Circulation of Geothermal Well - Apriyansah Toni; Astra Agus Pramana; Bambang Kustono (Penerbitan Universitas Trisakti, 2018)
Loss circulation is a major problem and known as the biggest challenge during drilling and well construction.This can leadsto various consequences,such as stuck pipe, loss of material and time to combat the losses, and even losing the well itself. Severe loss circulation conditions are often met while drilling geothermal wells in Indonesia. Partial to total losses have start experienced since drilling the surface section. Cement plugs is one of the conventional methods to cure losses. Number of cement plugs differ from one well to another well. Even in some wells, number of cement plugs performed for loss circulation plug can be over 30 times with total of more than 4,000 barrels of cement slurry pumped. Solution other than basic loss circulation material and cement plug must be developed to optimize curing loss time. Engineered fiber base concentration which is include; Base Fluid, LCM and Solid Package was obtained from simulation, then trial and error in laboratory was conducted. Based on the final recipe, the control pill was able to hold pressure and not leaking, even when using 5 mm grid clearance. Additional combined stiff fiber and flexible fiber with concentration of 6 lbs/bbl sufficient to hold exessive loss circulation.